Speech Discrimination as a Function of Age - R, Manimegalai (Journal of All India Institute of Speech and Hearing)
Gerontologists believe that the aging process begins even before we are born. Though some recent studies (Bergmon, 1967) indicate that our sensitivity for puretones increases till puberty and thereon there is a slight decline especially around 4 KHz. In addition to the progressive deterioration in the sensitivity for puretones generally atributed to presbycusis, the gereatric patient also typically demonstrate a reduced abitlity to understand the spoken language. This problem seems to be compatible with the account of puretone hearing loss.